Theory within a Policy. Dissecting Capacity Development, Harvesting Knowledge Stances - Alejandro Balanzo-Guzman (Tecnoscienza, 2017)
This essay unpacks capacity development policies, discussing its core rationales and building theory out of its main conceptual assumptions. Capacity development focuses on addressing and improving the elusive terms, qualities and means of "capacity" needed for lasting development. The essay addresses the following questions: what are the core rationales of capacity development? What theoretical sources lay within capacity development? Is it possible to distil analytical synthesis from these theoretical sources? It draws upon the understanding of agency as described by capacity development. Its theoretical foundations are extracted and discussed, building a single corpus: the knowledge stance perspective is proposed to observe meso-level agency. It builds on institutional work and innovation intermediation scholarly streams. The knowledge-stances perspective on agency shows a set of knowledge stances as analytical tools. Stances of boundary exploration, boundary setting and practice work are shown as forms of enacting, positioning and expanding a practice field. Stances of knowledge exploration, intermediation and supply are shown as strategies to enlarge its cognitive base. The theoretical value of this perspective accounts for a twofold purpose. First, addressing the realms of knowledge at stake in meso-level interaction, as a means to deepen conceptual reach on the myriad of discourses currently fostering change. Second, promoting a scope of practice and research that allows framing (capacity) development beyond the project level and the donor-focused scope.